6 JavaScript projects - Lehr, Michaela (SitePoint, 2018)
There's no doubt that the JavaScript ecosystem changes fast. Not only are new tools and frameworks introduced and developed at a rapid rate, the language itself has undergone big changes with the introduction of ES2015 (aka ES6). Understandably, many articles have been written complaining about how difficult it is to learn modern JavaScript development these days. We're aiming to minimize that confusion with this set of books on modern JavaScript. This book presents six complete JavaScript projects; each taking advantage of modern JavaScript and its ecosystem. You'll learn to build several different apps, and along the way you'll pick up a ton of useful advice, tips, and techniques. It contains: Build a Full-Sphere 3D Image Gallery with React VR by Michaela Lehr Build a WebRTC Video Chat Application with SimpleWebRTC by Michael Wanyoike Build a JavaScript Single Page App Without a Framework by Michael Wanyoike Build a To-do List with Hyperapp, the 1KB JS Micro-framework by Darren Jones Use Parcel to Bundle a Hyperapp App & Deploy to GitHub Pages by Darren Jones Interactive Data Visualization with Modern JavaScript and D3 by Adam Janes This book is for all front-end developers who wish to improve their JavaScript skills. You'll need to be familiar with HTML and CSS and have a reasonable level of understanding of JavaScript in order to follow the discussion.
Includes bibliographical references. - Online resource; title from PDF title page (EBSCO, viewed June 11, 2018)
Keywords: JavaScript (Computer program language); JavaScript (Langage de programmation); COMPUTERS; Programming Languages; JavaScript